Re: Questionable evidence of effectiveness of a national cardiovascular disease risk assessment program - Artac, M; Dalton, A; Majeed, A; Millett, C (2014)
•Despite a number of limitations to our study findings, we were careful in interpreting the findings and presented them in a balanced manner.•We argue that secular trends in risk factors may not have large impact on the changes in risk in our study.•We suggest that regression to the mean does not account for the observed changes in risk.•We argue that our title was not suggestive that the program was effective, but explores the impact of the program. © 2013 .